Multi-metal oxide catalyst for electrochemical water oxidation - Phang, Yi Fei (Nanyang Technological University, 2022)
Increasing popularity in hydrogen economy and environment sustainability as an alternative source for energy is strategic for bringing greenhouse gas emissions to net zero. Water splitting process is promising technology for producing hydrogen compared to steam methane reforming. However, the process is limited by sluggish oxygen evolution reaction kinetics which could be overcome by an effective electrocatalyst.